Effect of Oxygen vs Room Air on Intrauterine Fetal Resuscitation: A Randomized Noninferiority Clinical Trial. Issue 2 (February 2019) - Raghuraman, Nandini; Wan, Leping; Temming, Lorene A.; Woolfolk, Candice; Macones, George A.; Tuuli, Methodius G.; Cahill, Alison G.
Abstract : (Abstracted from JAMA Pediatr 2018;172(9):818–823) Category II fetal heart tracings are defined by the National Institute of Child Health and Human Development as a broad class of electronic fetal monitoring observed in more than 80% of laboring patients. This categorization does not necessarily predict neonatal acidemia, but the presence of category II fetal heart tracings often results in intrauterine resuscitation efforts aimed at improving fetal oxygenation.